Private Sphere in the Age of Digital Communication: Some Normative Aspects of Our Right to Privacy (Papers in Arts and Humanities, 2021)
Examining the interpretations on the “U.S. observation case,” I am trying to answer the question of which contemporary theory may serve as the adequate context for telling the story of the birth of our right to privacy and the modern power structures endeavoring to oppress this right. Relying on the relevant literature, I have attempted to reconstruct twopossible theories in light of the strength of the relationship between privacy and power: the paradigm rooted in the sociology of work; and one judicial approach based on human dignity. The analysis of the two privacy paradigms in contrast with each other highlights their advantages and disadvantages. I also attempt to outline normative points of viewrelevant when analyzing the relationship between power and privacy in the digital age.
Keywords: privacy; digital communication; sociology of work; human dignity; social philosophy